Agricultural landscapes must include at least 20% of natural habitats: benefits for pollinators and crop pollination - Garibaldi, Lucas Alejandro (2019)
Governments around the world increasingly acknowledge the need for better policy instruments to enhance natural and semi-natural habitats (NSH) within agricultural landscapes. However, the area of NSH that is required can vary enormously across nations, even when agroecological conditions are similar. This variation reflects complicated political, social, economical, and cultural trends across countries, but also results from the lack of clear guidelines from the global scientific community. Such guidelines are urgently needed, as NSH are quickly decreasing in agricultural landscapes worlwide. Indeed, the destruction of NSH has been identified as a principal cause of lower and less stable crop yields, and the loss of many of nature’s contributions that are essential for good quality of life. Here we propose that NSH must comprise at least 20% of the area of agricultural landscapes and discuss the benefits for pollinators and crop pollination.